Contralateral and Ipsilateral Interactions in the Somatosensory Pathway in Healthy Humans - Ishii, Daisuke; Ishibashi, Kiyoshige; Yuine, Hiroshi; Takeda, Kotaro; Yamamoto, Satoshi; Kaku, Yuki; Yozu, Arito; Kohno, Yutaka (Frontiers in Systems Neuroscience, 2021)
Hyper-adaptability, the ability to adapt to changes in the internal environment caused by neurological disorders, is necessary to recover from various disabilities, such as motor paralysis and sensory impairment. In the recovery from motor paralysis, the pre-existing neural pathway of the ipsilateral descending pathway, which is normally suppressed and preserved in the course of development, is activated to contribute to the motor control of the paretic limb. Conversely, in sensory pathways, it remains unclear whether there are compensatory pathways which are beneficial for the recovery of sensory impairment due to damaged unilateral somatosensory pathways, such as thalamic hemorrhage,. Here, we investigated the interaction between left and right somatosensory pathways in healthy human using paired median nerve somatosensory evoked potentials (SEPs). Paired median nerve SEPs were recorded at CP3 and CP4 with a reference of Fz in the International 10–20 System. Paired median nerve stimulation with different interstimulus intervals (ISI; 1, 2, 3, 5, 10, 20, 40, 60, and 100 ms) was performed to test the influence of the first stimulus (to the right median nerve) on the P14, P14/N20, and N20/P25 components induced by the second stimulus (left side). Results showed that the first stimulation had no effect on SEP amplitudes (P14, P14/N20, and N20/P25) evoked by the second stimulation in all ISI conditions, suggesting that there might not be a neural connectivity formed by a small number of synapses in the left–right interaction of the somatosensory pathway. Additionally, the somatosensory pathway may be less diverse in healthy participants.